The use of artificial intelligence algorithms to detect macroplastics in aquatic environments: A critical review - (:unkn) unknown (Elsevier BV, 2024)
The presence of macroplastic (MP) is having serious consequences on natural ecosystems, directly affecting biota and human wellbeing. Given this scenario, estimating MPs' abundance is crucial for assessing the issue and formulating effective waste manage...
Keywords: Macroplásticos; Inteligencia artificial